MEASUREMENT OF THE INCLINATION OF THE EARTH'S SURFACE NEAR A BLAST EPICENTER - Grayzer V.M.; Kuznetsov O.P.; Nedoshivin N.I.; Sultanov D.D. (My University, 1989)
We describe a method of detecting seismic oscillations comprised of both displacements and rotations, and we present examples of its application in the laboratory and in the epicentral zone of a shot. We built a model accelerographic device for direct optical recording of ground movements. It consisted of five pendulum accelerometers, two designed to record vertical oscillation and three to record horizontal oscillations. A series of experiments was performed on a vibrating platform with the above accelerometric apparatus. The true motion of the platform was in satisfactory agreement with the calculated translational movements and inclinations.